ASSESSMENT OF FOOD HANDLERS’ KNOWLEDGE AND HYGIENE PRACTICES AT SOME SELECTED TERTIARY INSTITUTIONS IN KANO STATE, NIGERIA - Garba, Yusuf Idris; Yahaya, Mustapha Mohammed (FUDMA JOURNAL OF SCIENCES, 2025)
Anybody concerned about eating healthy food and staying alive should pay close attention to food hygiene because food-borne illnesses can occasionally be very serious. This study evaluated food handlers’ knowledge and awareness of food hygiene as well as their practice of it. It was conducted among food handlers at a few chosen tertiary institutions in Kano State, Nigeria. A descriptive study with a cross-sectional design was conducted with 79 food handlers who fulfilled the inclusion criteria. With the assistance of research assistants, data was gathered with the aid of questionnaires, and the Statistical Program for Social Sciences (SPSS) was used for analysis. According to the results of this study, food hygiene practices are fair when it comes to major water sources, changing the water used to wash utensils, and disposing of waste, but they are good when it comes to hand washing. The handlers exhibited a fair certain level of knowledge and awareness regarding food hygiene. The study’s findings indicate that food handlers have a fair level of food hygiene knowledge and practice. However, improvements can yet be made in terms of food handler education and training, additionally frequent visits by environmental health officers (inspectors) to assess the handlers’ level of hygiene practice.